Climate Change Socioeconomic Impacts: The Case of Egypt - Al-Riffai, Perrihan (2017)
This was presented at the IFPRI Egypt Seminar, How to Make Agriculture Climate Smart in Egypt: A Macro Sector and a Household Perspective, held in partnership with Bibliotheca Alexandrina